Institutional convergence of CIS towards European Benchmarks - Inna Melnykovska; Andrea Gawrich; Thorsten Drautzburg (Center for Social and Economic Research (CASE), 2008)
The empirical analysis of the determinants of institutional development in transition countries as well as the qualitative country studies summarized in this publication allow for some optimism concerning a potential impact of the EU on institution building and governance quality in CIS countries. Regression analysis reveals a positive impact of EU cooperation agreements below a membership perspective. Alternatively to the EU, entry into the NATO accession process also exerts incentives for better institutions which are often overlooked. In contrast, WTO membership is not found to have any impact on institution building in CIS countries. While there is room for some EU-related optimism given the results from the regression analysis it depends on the country-specific ENP action plans and programs whether or not ENP cooperation actually leads to Europeanization or institutional convergence towards EU standards in the CIS. The case studies on the effectiveness of Neighborhood Europeanization through ENP in Ukraine, Georgia, and Azerbaijan reveal that current EU policies towards these countries can be, at best, seen as a catalyst but not as a main driver of institutional convergence. A perspective for a stake in the internal market is on the long horizon for Ukraine only. ENP mechanisms for conflict resolution in Georgia and Azerbaijan have been rather weak before the recent clash in Abkhazia and South Ossetia. The top-down institutional convergence, i.e. an EU-first strategy, worked well for Enlargement Europeanization but implemented in the ENP it significantly reduces the leverage of the EU to create a ring of well-governed neighbour states.
Keywords: F15; F20; F50; P20; P30; O19; 330; Europeanisation; European Union; European Neighborhood Policy; Institutional Convergence; Institutionelle Infrastruktur; Institutioneller Wandel; Wirtschaftsintegration; Rechtsangleichung; Europäische Nachbarschaftspolitik; EU-Staaten; GUS-Staaten